2021
DOI: 10.1155/2021/5572389
|View full text |Cite|
|
Sign up to set email alerts
|

Application Analysis of Wearable Technology and Equipment Based on Artificial Intelligence in Volleyball

Abstract: Today, while people’s satisfaction with materials is high, the pursuit of health has begun and sports are becoming increasingly important. Volleyball is a good physical and mental exercise, which helps improve the health of the body. However, excessive exercise usually leads to muscle strain and more serious accidents. Therefore, how to effectively prevent excessive fatigue and sports injuries becomes more and more important. In the past, some methods of exercise fatigue detection were mostly self-assessment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The mean recognition rate was 93.58%. Compared with the study report of Shangbin Li [ 27 ] (Reconition rate: 83.15–93.62%), the recognition rate of the model in this paper is improved. By comparison with the results based on pure sEMG and pure ECG signals, the model based on feature fusion shows better recognition precision and performance.…”
Section: Discussionmentioning
confidence: 59%
“…The mean recognition rate was 93.58%. Compared with the study report of Shangbin Li [ 27 ] (Reconition rate: 83.15–93.62%), the recognition rate of the model in this paper is improved. By comparison with the results based on pure sEMG and pure ECG signals, the model based on feature fusion shows better recognition precision and performance.…”
Section: Discussionmentioning
confidence: 59%
“…In modern volleyball, data-based modeling is critically important for enhancing training methodologies and game strategies. Aldous et al [40] and Ntzoufras et al [41] are developing stochastic and Bayesian methods for analyzing game dynamics, while Dai et al [42] and Yuan et al [43] are exploring the role of technological innovations in analyzing volleyball techniques. Endriani et al [44] proposes a model based on Umbrella Learning, while Leng et al [45], Li et al [46], and Wang et al [47] use random matrix models for analyzing learning and gameplay actions.…”
Section: Modeling In Volleyballmentioning
confidence: 99%
“…A set of studies [40,41] employ stochastic and Bayesian frameworks, including Markov chains and set difference prediction models, to dissect game dynamics. The integration of cuttingedge technologies, such as artificial intelligence and wireless communication networks, in analyzing and fine-tuning volleyball techniques and strategies is the focus of research [42,43]. Endriani et al [44] put forth a lower pass model anchored in the Umbrella Learning paradigm.…”
mentioning
confidence: 99%
“…5 When the related literature is reviewed, it is observed that studies were conducted on numerous subtopics such as the prediction of match results using the machine learning approach, the use of artificial neural networks in sports biomechanics, the creation of algorithms through collecting electrocardiography and electromyography signals to determine exercise fatigue and the prevention of fatigue and injury during exercise, the creation of soccer teams and transfer support using the machine learning approach, making strategic decisions and building the best team, the investigation of professional soccer players' wages, the direction of coaching experience, and the enhancement of player performance. [6][7][8][9][10][11][12][13] Artificial intelligence refers to the technology that imitates human tasks and uses machine learning to identify how these tasks will be imitated. 14 The data analytics focus of machine learning involves artificial intelligence making inferences from computer experience as well as learning by itself and playing a supporting role.…”
mentioning
confidence: 99%